2003
DOI: 10.1038/sj.ejcn.1601557
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional deficiencies in German middle-class male alcohol consumers: relation to dietary intake and severity of liver disease

Abstract: Objective: The purpose of the present study was to compare the nutrient intake and the nutritional status between German middle-class alcohol consumers and non-drinkers. Design: Cross-sectional study using patients with different stages of alcoholic liver disease (ALD) and healthy volunteers. Setting: Southern Germany. Subjects: Seventy-six hospitalized German middle-class alcohol consumers with different stages of alcoholic liver disease (ALD) and 22 healthy control subjects. Methods: Subjects and controls we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 38 publications
(70 reference statements)
0
34
0
Order By: Relevance
“…An alcohol-related effect on zinc plasma level was not found despite the involvement of zinc in alcohol metabolism and given that zinc intakes in drinkers are generally reported lower than in nondrinkers (Bergheim et al, 2003). Drinkers exhibited higher serum selenium level than nondrinkers as opposed to some previous reports (JablonskaKaszewska et al, 2003;Manari et al, 2003).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…An alcohol-related effect on zinc plasma level was not found despite the involvement of zinc in alcohol metabolism and given that zinc intakes in drinkers are generally reported lower than in nondrinkers (Bergheim et al, 2003). Drinkers exhibited higher serum selenium level than nondrinkers as opposed to some previous reports (JablonskaKaszewska et al, 2003;Manari et al, 2003).…”
Section: Discussionmentioning
confidence: 64%
“…Most of the studies report that alcohol consumption result in reduced antioxidant vitamin intakes and status (Bergheim et al, 2003;Manari et al, 2003). However, in the French cohort of the European Prospective Investigation into Cancer and Nutrition (E3N-EPIC) involving 100 000 middle-aged, highly educated women (Kesse et al, 2001), after adjustment for energy derived from alcohol, increasing alcohol consumption was associated with higher intake of vitamin E.…”
Section: Discussionmentioning
confidence: 99%
“…Under toxic condition (e.g. alcohol abuse) selenium levels of liver tissue decreased (25). Thus, SBP substitution in toxic-induced fibrosis may yield a therapeutic strategy targeted against SBP downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…α-tocopherol supplementation to rats chronically exposed to ethanol has been shown to prevent the formation of Mallory bodies and inflammatory infiltration of the liver but not increased apoptosis, inspite of increased antioxidant gene expression [6]. Several groups have shown that subjects with alcoholic liver disease have been shown to have significantly lower plasma vitamin E levels [9,37,38] and a higher degree of redox imbalance [7]. However, the results of long-term vitamin E supplementation have been controversial and inconsistent [5,14,39,40] although positive results have been reported in patients with non-alcoholic fatty liver [20,21].…”
Section: Discussionmentioning
confidence: 99%